Pengalaman Penyandang Diabetes Mellitus Tipe 2 dalam Melaksanakan Manajemen Diri Diabetes untuk Menjaga Kestabilan Glukosa Darah - Himmatul Khaira (Ameena Journal, 2025)
Although education has been given, there are still behaviors that are not in accordance with self-management in diabetes. So this study aims to explore the application of self-management in patients with diabetes mellitus to maintain stable blood glucose levels. This study uses a phenomenological approach with semi-structured interviews with 10 people with type 2 diabetes. The themes found in this study are clinical symptoms that determine the application of diabetes self-management, lack of motivation in the implementation of diet and activity management, the role of family in diet management. diabetes, the achievement of diabetes self-management has not been as expected, and psychological conditions that hinder diabetes self-management. The application of diabetes self-management in patients needs to be identified and evaluated further in order to help people with type 2 diabetes in determining the problem and finding the best solution to achieve stable blood glucose levels.